Analytical solution for one-dimensional vertical electro-osmotic drainage under unsaturated conditions. (January 2019) - Wang, Liujiang; Wang, Yaoming; Liu, Sihong; Fu, Zhongzhi; Shen, Chaomin; Yuan, Weihai
Abstract: In this study, exponential functions were incorporated in a one-dimensional model to represent the relationships of hydraulic and electro-osmotic conductivities with matric suction and the soil-water characteristic curve. Analytical solutions for pore water pressure, water content and drainage were derived, and laboratory tests were performed to verify the effectiveness of these solutions. Finally, a parametric study indicated that the soil-water characteristics of the soil had a remarkable impact on the drainage behaviour of electro-osmosis under unsaturated conditions and that the proposed analytical solutions could be used to design electro-osmotic drainage systems in unsaturated soils.